Pemberdayaan Perempuan Melalui Pelatihan Kewirausahaan dan Manajemen di GPKdi Naviri Kelurahan Tingkulu Kecamatan Wanea Kota Manado Provinsi Sulawesi Utara - Rumawas, Wehelmina (Universitas Sam Ratulangi, 2021)
The main problem of women, mothers and young women in the GPKdI Naviri Congregation, Tingkulu Village is the lack of skills and management in doing business. With potential natural resources and human resources, entrepreneurship training is necessary. The purpose of this community partnership program (PKM) activity is to provide knowledge and understanding of entrepreneurship and foster an entrepreneurial mentality. This training is also to motivate partners to be able to take advantage of the natural resources that are around them. The result of this activity was an increase in knowledge and understanding of entrepreneurship as well as the enthusiasm to become entrepreneurs, as well as the formation of entrepreneurial groups.Keywords:empowerment, women, entrepreneurs, training, managementÂ AbstrakMasalah utama perempuan, ibu dan remaja putri di Jemaat GPKdI Naviri Desa Tingkulu adalah kurangnya keterampilan dan manajemen dalam berbisnis. Dengan potensi sumber daya alam dan sumber daya manusia, pelatihan kewirausahaan sangat diperlukan. Tujuan dari kegiatan program kemitraan masyarakat (PKM) ini adalah untuk memberikan pengetahuan dan pemahaman tentang kewirausahaan dan menumbuhkan mental kewirausahaan. Pelatihan ini juga untuk memotivasi mitra agar dapat memanfaatkan sumber daya alam yang ada di sekitar mereka. Hasil dari kegiatan ini adalah peningkatan pengetahuan dan pemahaman tentang kewirausahaan serta semangat untuk menjadi wirausaha, serta terbentuknya kelompok wirausaha.Kata kunci: pemberdayaan, perempuan, wirausaha, pelatihan, manajemen